Anthony A. Long. Selfhood and Rationality in Ancient Greek Philosophy: From Heraclitus to Plotinus. New York: Oxford University Press, 2022. - Vertzagia, Despina (Conatus - Journal of Philosophy, 2023)
Anthony A. Long’s recent book, Selfhood and Rationality in Ancient Greek Philosophy: From Heraclitus to Plotinus (2022), is a collection of fourteen essays that explore the themes of selfhood and rationality in ancient Greek philosophy. Long’s book provides an illuminating account of the vast ancient Greek tradition and an engaging tour that begins with pre-Socratic thought and ends with Stoicism and Neoplatonism seeking answers to the multifaceted question of the rational self, its emergence and evolution within Greek antiquity.